Evaluation of Rental Flats Performance in Bandung City Based on Health Performance Indicators and Their Influence on Occupant Satisfaction - Ramadhan, Gilang; Angestiwi, Tiafahmi (Inovbiz: Jurnal Inovasi Bisnis, 2023)
Rental flat development is an alternative solution to solve the affordable housing problem in Indonesia’s big cities. Bandung City is one of the cities that really needs vertical residential development because it has a population of more than 2 million people and land availability is increasingly scarce. Apart from its basic function as a residence, flats must also have good health performance in order to fulfill all the aspects that residents need. This research aims to evaluate the performance of flats in Bandung City based on health performance indicators and their influence on occupant satisfaction. The assessment of flat health performance includes physical, mental, social, and managerial aspects. Descriptive research methods with qualitative and quantitative approaches were employed to evaluate the performance of the flats. Moreover, regression analysis was also carried out to determine the effect on resident satisfaction. The data collection techniques used were questionnaires, interviews, observation, and documentation studies. The results of the descriptive analysis show that flats in Bandung City have good health performance based on physical, mental, social, and managerial aspects. Furthermore, the variables that significantly influence occupant satisfaction are mental and managerial aspects. Meanwhile, the physical and social aspects have no significant influence on occupant satisfaction.